Memahami Pancasila Sebagai Bagian Tafsir Ajaran Islam: Dalil Teks Dan Konteks - Fathoni Fathoni; H.S. Tisnanta (Postgraduate State Islamic Institute (IAIN) Metro, 2018)
Understanding Pancasila as an open ideology, certainly can not be separated from the interpretation (hermeneutics/tafsir) in the text and context. When reading is interpreted as a physical process of scanning a line of words in the text by the sense of sight and digested by the brain, then understanding is the result of a set of reading processes to the text. There will always be a gap of understanding